Hubungan Permainan Finger Painting Terhadap Kreativitas Anak Di TK Al Islam 14 Mojosongo Kecamatan Jebres Surakarta Tahun Ajaran 2015/2016 - Betti Pratiwi, Fatimah, Drs. Ilham Sunaryo, M.Pd AUD, Junita Dwi Wardhani, SE. M,Ed (2016)
TERDAPAT HUBUNGAN ANTARA PERMAINAN FINGER PAINTING TERHADAP KREATIVITAS ANAK DI TK AL ISLAM 14 MOJOSONGO Fatimah Betti P, Ilham Sunaryo dan Junita Dwi Wardhani PG-PAUD, FKIP, UNIVERSITAS MUHAMMADIYAH SURAKARTA Pokingfatimah@yahoo.co.id ABSTRACT Fatimah Betti P / A52010084. THAT THERE IS A GAME CONNECTION FINGER PAINTING ON CREATIVITY OF CHILDREN IN KINDERGARTEN AL ISLAM 14 MOJOSONGO. Essay The Faculty of Education University of Muhammadiyah Surakarta, April 2016. Early Childhood Education, known as preschool education is education by providing the opportunity for children to be able to enjoy his world, is done through the provision of educational stimulation to help the growth and development of children physically and mentally in order to have the readiness to enter further education. This study aims to identify their relationship to the game of finger painting in kindergarten children's creativity AL Islam 14 Mojosongo the District Jebres Academic Year 2015/2016 and to know how much the relationship game against the creativity of children finger painting in kindergarten AL Islam 14 Mojosongo Jebres District of Academic Year 2015 / 2016. This research uses descriptive quantitative research. This research was conducted in kindergarten AL Islam 14 Mojosongo District of Jebres to group B in the academic year 2015-2016. The research sample as many as 40 children from group B in kindergarten AL Islam 14 Mojosongo the District Jebres Academic Year 2015/2016. Sampling using simple random sampling. Collecting data using questionnaires and observation. Testing the hypothesis used product moment correlation analysis. Based on the analysis that there is a relationship between a game of finger painting in kindergarten children's creativity terhadapa AL Islam 14 Mojosongo the District Jebres Academic Year 2015/2016. This is evidenced by the results perarson correlation r value of 0.659 with a significance of 0.000 <0.01 (p = 0.000; p <0.01), which means that Ho is accepted, ix which means there is a relationship between creativity perminan finger painting with children in kindergarten AL Islam 14 Mojosongo the District Jebres Academic Year 2015/2016.